Preparation and characterisation of polyethersulfone/ hydrous ferric oxide mixed matrix membranes with improved hydrophilicity for treatment of oily waste water - Wan Ikhsan, Syarifah Nazirah; Abdullah, Norfadhilatuladha; Yusof, Norhaniza; Aziz, Farhana; Misdan, Nurasyikin; Wan Salleh, Wan Norhayati; Ismail, Ahmad Fauzi (AIDIC, 2017)
The rapid growth in oil and gas industry has led to the large production of oily wastewater. The massive amount of oily wastewater derived from the industry has raised concerns in community especially its adverse impact to the environment. Membrane technology has been in the spotlight in recent advancement to treat the oily wastewater. The major obstacle regarding the membrane technology is fouling due to surfactant adsorption and/or oil droplets plugging the pore, which would lead to a severe decline of the flux and rejection rate. HFO nanoparticles are incorporated into the PES membrane matrix with the aim to improve the hydrophilicity, water permeability as well as the antifouling properties of the membrane. HFO is abundant and easily obtained making it the perfect candidate in developing economical and energy saving membrane operation. Hydrous ferric dioxide (HFO) nanoparticles were synthesised via chemical precipitation method and incorporated in polyethersulfone (PES) to fabricate nanocomposite mixed matrix membranes (MMMs) for ultrafiltration (UF). The resulting membranes were characterised by SEM, FTIR, contact angle goniometer, before further subjected to water permeation test. It was found that contact angle of membrane decreased remarkably with an increase in HMO nanoparticle loading (state the value/ percentage decrement). The pore size at the skin layer however decreased as observed by SEM. As for the UF experiments, pure water permeation rate increased remarkably with increasing nanoparticle loading.